PENDIDIKAN AKHLAK MENURUT MAHMUD SYALTUT DALAM TAFSIR AL-AJZA’ AL-ASYRAH AL-ULA - Marpuah, Eva (TAFASIR: Journal of Quranic Studies, 2025)
Abstract This study aims to determine the thoughts of Sheikh Mahmud Syaltut's Moral Education through one of his books, namely the Book of Tafsir al-Ajza' al-Asyrah al-Ula. The method of this research is qualitative research with a Library Research approach or literature review, which is a study that utilizes library sources to obtain research data, not the results of interviews or direct observation. The results of this study indicate that Mahmud Syaltut's thoughts in moral education tend to create a good and ideal social order. His thoughts on good and bad according to morals are that humans are indeed created to have these two potentials in their lives. The good that humans do comes from their obedience to God's commands, while the bad that they do is due to their negligence in following the whispers of Satan. While his thoughts on justice, he defines justice as equality that must be carried out by all who exist in this universe according to the guidance of the sharia.Keywords:  (Mahmud Syaltut, Tafsir al-Ajza' al-Asyrah al-Ula, Moral Education)